From "Building the Ecosystem" to "Driven by Demand": How to Meet the Digital Scholarship Needs of Humanities Scholars - XIAO Peng (Nongye tushu qingbao xuebao, 2020)
[Purpose/Significance] The paper points out that "building the ecosystem" and "driven by demand" are two keywords for academic libraries to meet the digital scholarship needs of humanities scholars and build digital humanities services. Both of these require us to understand the strategic issues of digital humanities services for academic libraries from the macro perspective, and then explore the feasible path to construct a digital academic ecology from the macro and academic level. [Method/Process] Based on the early accumulation of the subject group and related cases, this paper discusses the necessity and possibility of constructing the ecosystem of digital humanities. [Results/Conclusions] The main conclusions include: (1) emphasizing the respect for objective realities, and regarding the construction of " ecosystem of digital humanities " as the primary goal; (2) clearing up the different types of digital academic needs of humanities scholars and carrying out the type study of academic libraries according to their needs; (3) academic libraries can be divided into leading academic libraries, academic libraries that play a supporting role and those at a basic level, and we should promote different types of academic libraries to perform their duties in the digital academic ecology, to meet different needs of humanities scholars, and to construct the ecosystem of digital humanities.